KINERJA APARATUR DALAM PENERBITAN SURAT PERINTAH MEMBAYAR (SPM) PADA BAGIAN KEUANGAN DINAS PENDIDIKAN DAN KEBUDAYAAN DAERAH PROVINSI SULAWESI TENGAH - Ulfah, Ulfah (Katalogis, 2015)
This research aimed at analysing the job performance of apparatus in issuing payment statement letter (SPM) and at describing the job performance of the Financial Section of the Provincial Office of Education and culture, Central Sulawesi. This was a qualitative research method attempting to find out the facts and phenomena in relation to the beroucratic job performance in issuing payment statement letter (SPM). In order to assess the job performance of apparatus, the researcher used five indicators by Agus Dwiyanto : produtivity, quality of service, responsiveness, responsibility, and accountability. The informants were the apparatur who understand and get involved in issuing the SPM. The primary data were collected directly from the informants and the secondary ones were obtained indirectly the techniques of data collection were interview, observation, and documentation. The data collection were interview, observation, and documentation. The data were analysed in three stages: data reduction, data presentation, and data conclusion. The research shows that job performance of the apparatus in issuing paymant statement letter (SPM) at the Financial Section of the Provincial Office of Education and Culture, Central Sulawesi has not been optimal. This is due to the lack of communication and coordination, as well as discrimination on the parts in proposing an SPM. This can been seen from the time spent in completing an SPM and from the level of the SPM cutumers satisfaction. It is effective when there is a handover of responsibility and job to the apparatus for processing an SPM. Additionally, the apparatus should work based on the standard operational procedure (SOP) in order to complete the job on the time and not being handled by only certain apparatus.